Investigation of Employee Performance Determinants Reviewing Competence and Organizational Culture with Performance Satisfaction as Intervening Variable - Hasugian, Sustih; Absah, Yeni; Sembiring, Maximus Gorky (Jurnal Maksipreneur, 2024)
This research intends to collect empirical data, facts, and information that are valid, accurate, and trustworthy regarding the Influence of Organizational Culture, Competence, and Learning on Employee Performance, causal studies at the Sibolga Navigation District Office Class III. This study was conducted from January to March 2022 utilizing a quantitative research strategy and survey methodology. This study's sample consists of 109 state civil servants and 86 state civil servants from the Class Navigation District Office. III Sibolga. Using a Likert Scale, the researchers determined the value of each question item across all variables, as well as the amount of the value provided in each statement. Path Analysis is used to assess data gathered via questionnaire distribution. Competence has a good and considerable impact on job satisfaction, organizational culture has a big impact on job satisfaction, and job satisfaction has a significant impact on performance, according to the findings of this study.